2014
DOI: 10.13080/z-a.2014.101.056
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of chlorophyll fluorescence in different leaf positions may detect nitrogen deficiency in wheat

Abstract: Nitrogen deficiency strongly influences crop photosynthetic performance and biomass production. In this study, we applied rapid, non-invasive records of chlorophyll a fluorescence kinetics for evaluation of wheat (Triticum aestivum L.) leaf photosynthetic performance. Plants were grown during the whole season in big pots filled with the soil substrate and they were supplied by different doses of nitrogen nutrition. The plant nitrogen and leaf chlorophyll content as well as the plant aboveground biomass were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Several studies (Akhter et al, 2016, Sclichting et al, 2015, Živčak et al, 2014 have reported on faster and non-destructive new tools which characterize nitrogen status in plant. Optical properties of leaf pigments (chlorophyll and polyphenols) have been used as wheat plant nitrogen status indicators (Foxa, Piekieleka, & Macneala, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (Akhter et al, 2016, Sclichting et al, 2015, Živčak et al, 2014 have reported on faster and non-destructive new tools which characterize nitrogen status in plant. Optical properties of leaf pigments (chlorophyll and polyphenols) have been used as wheat plant nitrogen status indicators (Foxa, Piekieleka, & Macneala, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Related studies showed that the characteristic peaks of LIF spectra were closely related to the nutrient stress of crops (Tuba et al 2010, Yang et al 2015a). Due to the advantages of rapid, non-destruction and without pre-processing analysis, it has been widely used to estimate canopy N status of maize, tomato, wheat and paddy rice , Yang et al 2015b, Živčák et al 2014a). However, they mainly focused on using the far-red and red fluorescence ratios, fluorescence intensity as well as non-photochemical quenching etc.…”
mentioning
confidence: 99%
“…Janušauskaitė and Feizienė (2012) have found that nitrogen deficiency could be noticed by investigating the Fv/Fm ratio. Some authors disagree that although Fv/Fm contains valuable information on the status of photosynthetic apparatus, it can be non-specific and often insensitive to many environmental effects (Lawlor, 2002, Brestic et al, 2012, Živčák et al, 2014. Our findings also show that photosystem II efficiency of V. faba increased with increasing sapropel concentration in the soil; however, the increase was insignificant (r = 0.94; p > 0.05) (Figure 1).…”
Section: Resultsmentioning
confidence: 42%